Comparative Assessment of Hallux Rigidus using Conventional Radiograph and Weightbearing CT. Issue 1 (January 2022) - Lee, Hee Young; Lalevee, Matthieu; Mansur, Nacime S.; Dibbern, Kevin N.; Ehret, Amanda; Maly, Connor; Hembree, Walter C.; Femino, John E.; Vivtcharenko, Victoria; Netto, Cesar de Cesar
Category: Midfoot/Forefoot Introduction/Purpose: The etiology of hallux rigidus (HR) is not well understood and Its association with first-ray hypermobility, hallux valgus and metatarsus primus elevatus (MPE) has not been clearly proven. MPE, elevated first metatarsal has been a topic of debate since Lambrinudi`s first description. Recent studies have supported MPE in hallux rigidus by measuring with various methods on wightbearing lateral radiographs, but there are limitations of conventional radiography due to variation in X- ray projection and superimposed metatarsals regardless of the methods of measurement. Our objective was to assess MPE and other associated parameters with hallux rigidus via radiography and WBCT for convergent validity and to evaluate the use of classification system used in conventional radiography with WBCT. Methods: This is a single-center, retrospective study from prospectively collected data. 20 symptomatic hallux rigidus patient with weightbearing radiograph and WBCT were enrolled from October 2014 to December 2020. Measured parameters included hallux valgus angle (HVA), intermetatarsal angle (IMA), hallux interphalangeal angle (HIPA), distal metatarsal articular angle (DMAA), 1st TMT joint version, First and second metatarsal lengths, Metatarsus adductus angle, 2nd cuneiform-2nd metatarsal angle, Talus-1st Metatarsal Angel, First and second metatarsal declination angles, and MPE. MPE was measured as the direct distance between 1st and 2nd metatarsals (modified Horton index). All patients were graded according to the radiographic criteria of Coughlin and Shurnas classification on radiographs and WBCT, separately. Paired T-test was performed to compare radiographic measurements with WBCT. Results: Mean age was 55.9, 12 males and 8 females. HVA (15.73 in X-ray vs 14.04 in WBCT), AP first TMT version (16.25 vs 16.47), 2nd cuneiform-2nd metatarsal angle (24.54 vs 26.60), Talus-1st Metatarsal Angel (-7.67 vs -7.89) were not different between radiograph and WBCT. MPE was measured higher in WBCT by 0.86 mm compared to radiograph. First metatarsal declination angle was lower in WBCT by 2.9° indicating increased MPE. When graded with radiographic findings, 5 (25%) patients were grade 1, 5 (25%) patients were grade 2 and 10 (50%) grade 3, when graded with WBCT, 1 (5%) patient had grade 1, 3 (15%) patients were grade 2 and 16 (80%) grade 3. Dorsal subluxation/translation of first metatarsal at first TMT joint was observed 3 (15%) in radiograph and 9 (45%) in WBCT. Conclusion: HVA, AP first TMT version, 2nd cuneiform-2nd metatarsal angle, Talus-1st Metatarsal Angel demonstrated consistent measurements in radiograph and WBCT. MPE was measured higher in WBCT when measured with direct distance (0.86 mm) between the first and second metatarsals using modified Horton index and first metatarsal declination angle (2.9°). When graded with WBCT, the subchondral cyst in the proximal phalanx and metatarsal head were better delineated leading to higher grade in WBCT. Further studies are needed for inter-rater reliability and discriminant validity of the measurements determined by differences between different groups (HR vs control).